Phosphatase UBLCP1 is required for the growth, virulence and mitochondrial integrity of Toxoplasma gondii - Kaiyin Sheng; Kaiyue Song; Yimin Yang; Haiyan Wu; Zhendong Du; Xueqiu Chen; Yi Yang; Guangxu Ma; Aifang Du (Parasites & Vectors)
Abstract Background The mitochondrion is proposed as an ideal target organelle for the control of apicomplexan parasites, whose integrity depends on well-controlled protein import, folding, and turnover. The ubiquitin-like domain-containing C-terminal domain phosphatase 1 (UBLCP1) was found to be associated with the mitochondrial integrity in Toxoplasma gondii. However, little is known about the roles and mechanisms of UBLCP1 in this apicomplexan parasite. Methods The subcellular localization of UBLCP1 in the tachyzoites of T. gondii was determined by an indirect immunofluorescence assay. The roles of UBLCP1 in the growth, cell cycle, and division of T. gondii were assessed by knocking out this molecule in the tachyzoites. Comparative phosphoproteomics between the UBLCP1-deficient and wild-type tachyzoites were performed to understand the roles of UBLCP1 in T. gondii. The virulence of UBLCP1-deficient tachyzoites of T. gondii was tested in mice. Results UBLCP1 is expressed in the nucleus and cytoplasm of T. gondii tachyzoites. Tachyzoites lacking UBLCP1 exhibit collapsed mitochondrion, decreased mitochondrial membrane potential, and compromised growth and proliferation in vitro. Proteins involved in protein turnover and intracellular trafficking have been found differentially phosphorylated in the UBLCP1-deficient tachyzoites compared with the control. Deletion of UBLCP1 also shows that this phosphatase is essential for the propagation and virulence of T. gondii tachyzoites. Mice immunized with UBLCP1-deficient T. gondii tachyzoites survived challenges with the virulent PRU or VEG strain. Conclusions UBLCP1 is required for the mitochondrial integrity and essential in the lytic cycle (e.g., host cell invasion and parasite replication) in vitro and the pathogenicity of this parasite in vivo. UBLCP1 is a candidate target for a vaccine or a drug for toxoplasmosis in animals. Graphical Abstract